Transcriptome analysis of transcription factors and enzymes involved in monoterpenoid biosynthesis in different chemotypes of Mentha haplocalyx Briq - Xin An; Jingqiong Wan; Hui Jiang; Yangzhen Liao; Chang Liu; Yuan Wei; Chongwei Wen; Zhen Ouyang (PeerJ, 2023)
Background The main active ingredients of Mentha haplocalyx Briq. essential oils are monoterpenes. According to the component of essential oils, M. haplocalyx can be divided into different chemotypes. Chemotype variation is widespread in Mentha plants but its formation mechanism is unclear. Methods We selected the stable chemotype l-menthol, pulegone, and carvone of M. haplocalyx for transcriptome sequencing. To further investigate the variation of chemotypes, we analyzed the correlation between differential transcription factors (TFs) and key enzymes. Results Fourteen unigenes related to monoterpenoid biosynthesis were identified, among which (+)-pulegone reductase (PR) and (−)-menthol dehydrogenase (MD) were significantly upregulated in l-menthol chemotype and (−)-limonene 6-hydroxylase was significantly upregulated in carvone chemotype. In addition, 2,599 TFs from 66 families were identified from transcriptome data and the differential TFs included 113 TFs from 34 families. The families of bHLH, bZIP, AP2/ERF, MYB, and WRKY were highly correlated with the key enzymes PR, MD, and (−)-limonene 3-hydroxylase (L3OH) in different M. haplocalyx chemotypes (r > 0.85). The results indicate that these TFs regulate the variation of different chemotypes by regulating the expression patterns of PR, MD, and L3OH. The results of this study provide a basis for revealing the molecular mechanism of the formation of different chemotypes and offer strategies for effective breeding and metabolic engineering of different chemotypes in M. haplocalyx.